Design, construct and evaluate of a variable speed controller for a 180V DC motor - Wan Intan Khatijah Wan Abdul Aziz (Universiti Malaysia Perlis, 2009)
This project is to design, construct and evaluate of a variable speed controller for a 180V DC motor. Basically, the usage of this controller is to adjust the DC motor speed by adjusting or varying the frequency. Generally, for this project a LM555 timer IC component will be used to generate oscillation. There will be two inputs for the circuit. One will be the input for the oscillator and the other one will be the input for the DC motor. The input voltage for the oscillator is 13V whereas the input voltage for the DC motor is 180V. The voltage and current to the motor is controlled by a MOSFET. The MOSFET is controlled by a circuit controller that is capable of controlling the speed of a 180V motor by controlling the frequency.